Kabbalah and mysticism - Moreno-Szypowska, Jadwiga Clea (Filozofia Chrześcijańska, 2022)
The article "Kabbalah and mysticism" is divided into three parts, in which the general understanding of Kabbalah based on mysticism is presented. The first is devoted to the general definition of mysticism, wanting to reflect on this: Is Kabbalah one? In order to be able to answer this question, the author gives voice to the more important scholars of Judaism who have dealt with this issue or are still dealing with it. They are clearly characterizing what mysticism is, they try to create an equivalent explanation of Kabbalah, thus showing its specificity. Once confirmed that Kabbalah can be considered a kind of mysticism, the author moves on to the second part, in which she presents the basic sources of mysticism of Kabbalah. It discusses the most important items of rabbinic and non-rabbinic literature, showing how the non-rabbinic is continuator of the rabbinic. The third part of the article focuses on a deeper description of the initial types of mysticism: creation, chariot and body, which form the foundation for the later mysticism of word and letter. The mysticism of words and letters is kabbalah, that is, the hermeneutical art of biblical exegesis, based on the properties of the Hebrew alphabet and language, as God's tool for knowing Him. The article is based on the considerations of such authors as: Gershom Scholem, Roland Goetschel, Joseph Dan, Charles Mopsik, Marc-Alain Ouaknin, or the controversial Moshe Idel.